PETROLOGICAL AND PETROGRAPHIC CHARACTERISTICS OF BUTON ROCK ASPHALT (ASBUTON) TRAP ROCK IN THE WINNING AREA OF BUTON REGENCY - Isman Saleh (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to identify the petrological and petrographical characteristics of carbonate rocks that act as natural asphalt (Asbuton) reservoir rocks in the Winning area, Buton Regency. The analysis was conducted through megascopic observation of rock outcrops and microscopic observation of thin sections using a polarizing microscope. The results show that the carbonate rock units in the study area are dominated by bioclastic limestone (biomicrite) and dolomitic limestone (biogenic dolomite). The bioclastic limestone consists of foraminiferal and shell fragments bound by micrite and sparry calcite cement, whereas the dolomitic limestone displays fine- to medium-crystalline textures with well-developed intercrystalline porosity formed through dolomitization. Partial to advanced dolomitization occurred due to the circulation of magnesium-rich fluids in a restricted marine environment during the post-depositional stage. The mineralogical transformation from calcite to dolomite enhanced both porosity and compactness, making these rocks potential reservoir rocks for natural asphalt accumulation. Overall, the petrological and petrographical characteristics indicate that the carbonate rocks in the Winning area underwent a complex diagenetic evolution and play a significant role in the formation and entrapment system of Buton Rock Asphalt (Asbuton).